2-x/x-3整体+1/3-x=3(2)5x-4/2x-4=2x+5/3x-6整体-0.5解方程
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 15:47:10
2-x/x-3整体+1/3-x=3(2)5x-4/2x-4=2x+5/3x-6整体-0.5解方程
2-x/x-3整体+1/3-x=3(2)5x-4/2x-4=2x+5/3x-6整体-0.5解方程
2-x/x-3整体+1/3-x=3(2)5x-4/2x-4=2x+5/3x-6整体-0.5解方程
(2-x)/(x-3)+1/(3-x)=3
(2-x)/(x-3)-1/(x-3)=3
(2-x-1)/(x-3)=3
1-x=3x-9
4x=10
x=2.5
(5x-4)/(2x-4)=(2x+5)/(3x-6)-0.5
3(5x-4)/(6x-12)=2(2x+5)/(6x-12)-3
3(5x-4)/(6x-12)-2(2x+5)/(6x-12)+3=0
(15x-12-4x-10)+3(6x-12)=0
11x-22+18x-36=0
29x=58
x=2
经检验x=2是增根
1.
(2-x)/(x-3)+1/(3-x)=3
(2-x)/(x-3)-1/(x-3)=3
(2-x)-1=3(x-3)
2-x-1=3x-9
1-x=3x-9
1-x-3x+9=0
-4x+10=0
x=5/2
2.
(5x-4)/(2x-4)=(2x+5)/(3x-6)-0.5
(5x-4)/2(x-2)...
全部展开
1.
(2-x)/(x-3)+1/(3-x)=3
(2-x)/(x-3)-1/(x-3)=3
(2-x)-1=3(x-3)
2-x-1=3x-9
1-x=3x-9
1-x-3x+9=0
-4x+10=0
x=5/2
2.
(5x-4)/(2x-4)=(2x+5)/(3x-6)-0.5
(5x-4)/2(x-2)=(2x+5)/3(x-2)-0.5
3(5x-4)=2(2x+5)-0.5*6(x-2)
15x-12=4x+10-3x+6
15x-12=x+16
15x-12-x-16=0
14x-28=0
x=2
因为x=2时,方程分母为零,所以x=2是增根。
收起